Transforming Bangladesh's coastal agriculture needs bridging innovation with policy action - Ahmed, Sharif; Debnath, Manik; Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2025)
The coastal area of Bangladesh is situated in the lower floodplain of the Ganges delta and is highly vulnerable to rising sea levels, with an elevation of only about 2-3 meters above mean sea level. In addition to sea level rise, this region is particularly susceptible to cyclones, storm surges, and flooding. The coastal zone accounts for approximately 32% of Bangladesh's net cultivable land and is home to over 40 million people. Around 1.2 million hectares of coastal land are affected by varying levels of salinity.